Windows of sensitivity to toxic chemicals in the motor effects development() - Ingber, Susan Z. (Regul Toxicol Pharmacol, 2015)
Many chemicals currently used are known to elicit nervous system effects. In addition, approximately 2000 new chemicals introduced annually have not yet undergone neurotoxicity testing. This review concentrated on motor development effects associated with exposure to environmental neurotoxicants to help identify critical windows of exposure and begin to assess data needs based on a subset of chemicals thoroughly reviewed by the Agency for Toxic Substances and Disease Registry (ATSDR) in Toxicological Profiles and Addenda. Multiple windows of sensitivity were identified that differed based on the maturity level of the neurological system at the time of exposure, as well as dose and exposure duration. Similar but distinct windows were found for both motor activity (GD 8–17 [rats], GD 12–14 and PND 3–10 [mice]) and motor function performance (insufficient data for rats, GD 12–17 [mice]). Identifying specific windows of sensitivity in animal studies was hampered by study designs oriented towards detection of neurotoxicity that occurred at any time throughout the developmental process. In conclusion, while this investigation identified some critical exposure windows for motor development effects, it demonstrates a need for more acute duration exposure studies based on neurodevelopmental windows, particularly during the exposure periods identified in this review.